Developing a hybrid learning model for Indonesian language instruction integrating local wisdom: Evidence of validity and practicality - Harfiandi; Kasmi, Hendra; Priyatni, Endah Tri; Zahro, Azizatuz; Pranata, Didi Yudha (Journal of Education and e-Learning Research, 2026)
The increasing use of hybrid learning in language education has not been fully matched by the development of models that are sensitive to local social and cultural contexts. This study aims to develop and evaluate the Hybrid Mode Indonesian Language Learning (PBIMH) model through a formative research approach that positions teachers as co-designers throughout all stages of development. A total of 28 teachers from professional education programs in Banda Aceh and Aceh Besar were actively involved in the design process, limited trials, and iterative reflection. Data collection was carried out through expert validation, questionnaires, and reflective feedback to assess the validity and practicality of the model. The analysis results showed a high level of content and construct validity with an average of 4.51 (SD = 0.53), with expert construct assessments ranging from 87.5–95, which is classified as very acceptable. The practicality test showed a positive response from teachers, with an average score of 4.51 (SD = 0.58). The novelty of the research lies in the systematic integration of local wisdom into a hybrid learning structure through collaborative and formative mechanisms. PBIMH was deemed valid, practical, and provided a conceptual contribution to the development of context-based language learning.